Efforts to Improve Students' Learning Outcomes on Moral Aspects with Demonstration and RolePlaying Method at SMA Negeri Lawe Sumur - Sawabi, Ihsan (Jurnal Profesi Guru Indonesia, 2024)
This research aims to improve student learning outcomes in learning Islamic religious education by using demonstration and play methods. This research is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this research are high school students. The data of this research was obtained with test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze the learning activities of teachers and students. The data analysis technique used in this research is descriptive statistics by comparing the results obtained with research success indicators. The results of the research show that demonstration and play methods can improve student learning outcomes in learning Islamic religious education. This can be seen from the increase in the percentage of student learning completion in each cycle with details of the pre-cycle 44.71%, the first cycle 79.39% and in the second cycle it increased to 89.96%. Thus, the use of demonstration and play methods can be used as an alternative to improve student learning outcomes in Islamic religious education.